Chemical Methods for Selective Labeling of Proteins. Issue 40 (26th September 2019) - Rawale, Dattatraya G.; Thakur, Kalyani; Adusumalli, Srinivasa Rao; Rai, Vishal
Abstract : Protein bioconjugation poses outstanding questions of selectivity to the organic transformations. Besides, the presence of a pool of functional groups in the structural outfit of a protein brings its own set of characteristics. In this minireview, we highlight the challenges faced by a chemical transformation to deliver selectivity in the modification of proteins. The examples of pre‐engineered proteins outline the attributes associated with chemoselectivity and chemical orthogonality. Building on this foundation, we discuss the complexity of site‐selectivity in the single‐site modification of native proteins. The gradual evolution of chemical methods while addressing the challenges associated with different amino acids are outlined. The modular methods for labeling a residue independent of its reactivity order closes the discussion. Abstract : Single‐site protein bioconjugation requires an understanding of chemical reactivity, chemoselectivity, and site‐selectivity. This minireview covers examples in this perspective. It provides an understanding of principles that can help design new chemical technologies for precision engineering of proteins.